(untitled) (European journal of volunteering and community-based projects, 2026)
Purpose – This study explores judgment heuristics and cognitive biases in evaluative, judgmental, and decision-making processes within volunteer-based non-profit organizations. The aim is to assess whether and how the voluntary and non-profit nature of these entities can influence the frequency, intensity, and impact of these cognitive mechanisms. Design/methodology/approach – The author presents a theoretical-conceptual paper and a viewpoint that considers literature from various socio-economic disciplines. Findings – The contribution, in addition to reflecting on group decisions and obstacles to optimal choices, suggests that due to the potentially lower focus on direct economic outcomes and the often voluntary nature, in non-profit organizations characterized by less hierarchical relational dynamics, the use of heuristic processes with consequent cognitive biases could be more pronounced, even unconsciously, with potential repercussions on the quality of decisions. Research limitations/implications – Despite the lack of empirical investigation, the paper offers useful insights for improving awareness and active management of distorting cognitive phenomena in decision-making contexts. The social implications that arise should stimulate further experimental-comparative research with the methodologies described in this article. Originality/value – The originality lies in the application of heuristic and bias concepts to the non-profit sector, a rarely explored area but of great relevance for the quality of governance and participatory processes, as well as for the effectiveness and fairness of decision-making processes.